The effects of candidate probiotic strains on the gut environment in dextran sulfate sodium-induced colitis mouse - Kung Ahn; Kyung-Wan Baek; Kyeongeui Yun; Yunseok Oh; Yong Sung Kim; Eunok Im; Yunna Lee; Jieun Choi; Eun-Ji Song; Yong-Soo Park; Dong Ho Lee; Wonsuk Lee; et al. (Scientific Reports)
Abstract Inflammatory bowel disease (IBD) is a chronic condition characterized by intestinal inflammation and dysbiosis, with limited treatment options and significant challenges in long-term management. This study investigated the therapeutic potential of novel strains belonging to Bifidobacterium longum and Limosilactobacillus species, in a dextran sodium sulfate (DSS)–induced mouse model of colitis. In this study, our primary objective was to determine whether ingestion of these strains alleviates colitis symptoms and, if so, to elucidate how they restored gut microbial balance and modulated microbial metabolic functions. In most probiotic-treated groups, colitis disease activity index scores were significantly improved and colon length was preserved, with strains CBA7106 and BBH exhibiting efficacy comparable to that of the Lactobacillus rhamnosus GG (used as a positive control). Moreover, histological analyses confirmed reduced inflammation and enhanced mucosal integrity. Microbial diversity assessments demonstrated a marked restoration of gut microbial composition, highlighted by increased abundances of beneficial taxa such as Lactobacillus and Akkermansia. Metabolomic profiling identified key anti-inflammatory metabolites, including 6-hydroxycaproic acid, indole-3-lactic acid, and choline, which were significantly elevated in the probiotic-treated groups. Notably, functional analyses using PICRUSt2 revealed a sustained decrease in the siderophore biosynthesis pathway (ko01053), suggesting that these candidate probiotic strains may inhibit siderophore production—a pivotal mechanism by which pathogenic bacteria aggravate intestinal inflammation. Taken together, these findings indicate that the candidate probiotic strains CBA7106 and BBH effectively mitigate DSS-induced colitis by modulating the gut microbiota, promoting the production of anti-inflammatory metabolites, and suppressing siderophore biosynthesis. This study provides valuable insights into the development of targeted probiotic therapies for IBD, underscoring their potential as a complementary approach to restoring intestinal health and reducing inflammation. Further clinical studies are warranted to validate these observations in human populations.